Comparing Synchronus and Asynchronous Learning in Qur’anic Tahsin at Universitas Terbuka: A Study on Student Learning Outcomes and Processes - sariyani sariyani (International Journal of Islamic Education, Research and Multiculturalism)
Abstrak